Film production technique : creating the accomplished image / Bruce Mamer. - Mamer, Bruce (Wadsworth, 2002)
This text covers lighting, cameras, editing, crew organization, and the production process. It helps students understand difficult material and visualize the equipment and methods currently used in the film industry.